Kajian Aromaterapi Lavender dalam Mengatasi Nyeri pada Pasien dengan Post Operasi Open Fracture Calcaneus Sinistra: Studi Kasus - Fariman, Rani; Hartati, Kirana; Andriana, Susan; Afrizal, Hilman (Lembaga Publikasi Ilmiah Nusantara, 2024)
The calcaneus is the largest tarsal bone and functions to support the body. Calcaneal fractures are relatively rare, accounting for approximately 1–2% of all fractures. Prompt management is required for such fractures, often involving surgical intervention, which can result in postoperative pain. One method for managing this pain is through lavender aromatherapy. This study aims to evaluate the use of lavender aromatherapy relaxation techniques in reducing pain in patients following surgery for an open fracture of the left calcaneus. This research is a descriptive qualitative case study using a single-case design involving a patient who underwent surgery for an open fracture of the left calcaneus. The intervention involved administering a lavender aromatherapy relaxation technique, with pain levels assessed using the Numeric Pain Scale. The results showed that following the intervention — the use of lavender aromatherapy relaxation combined with analgesics — the patient's pain level decreased from a score of 5 to 3. The conclusion of this case study indicates that the application of lavender aromatherapy relaxation techniques combined with analgesics is easy to administer and effective in reducing pain levels in patients after surgery for an open fracture of the left calcaneus.